A review of group-based methods for teaching statistics in higher education. (9th March 2021) - Jones, Elinor; Palmer, Tom
Abstract: The teaching of statistics in higher education in the UK is still largely lecture based. This is despite recommendations such as those given by the American Statistical Association's Guidelines for Assessment and Instruction in Statistics Education report that more emphasis should be placed on active learning strategies where students take more responsibility for their own learning. One possible model is that of collaborative learning, where students learn in groups through carefully crafted 'problems', which has long been suggested as a strategy for teaching statistics. In this article, we review two specific approaches that fall under the collaborative learning model: problem- and team-based learning. We consider the evidence for changing to this model of teaching in statistics, as well as give practical suggestions on how this could be implemented in typical statistics classes in higher education.